The unmet needs of women with breast cancer: a qualitative research - Foà, Chiara; Guarnieri, Maria Cristina; Basciu, Valentina; Naldi, Silvia; Scaravella, Mariavittoria; Scirpoli, Antonietta (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work. Breast cancer (CM) is the most commonly diagnosed form of cancer in Italy and the most common malignancy in women (25%) with 53,000 new cases. This disease affects all age groups (1 in 40 women <49 years, 1 in 20 between 50 and 69 years, 1 in 25 between 70 and 84 years). The percentage of patients diagnosed with cancer within 5 years of diagnosis is higher than for other cancers, and this conviction rate in these cancer patients has increased, leading to an ever-improving level of attention. The research aims to understand the main needs of women with breast cancer, compare them with those reported in the literature and in particular to identify which of these are still unsatisfied. Method The study is based on the use of the narrative interview conducted by the Case Manager, in the Breast Unit of Melegnano (Milan), selected with a sampling of convenience.The participants who joined the research project were 12 women with breast cancer, aged between 40 and 60, who are in the active treatment phase of the disease. Results. As highlighted by literature, various unmet needs have emerged, afferent to well-defined areas: emotional health, continuity of care, information, adverse effects, educational strategies, economics, information and social support. The study showed that, the needs that are most unsatisfied relate to the information area and the psychological area. Conclusion. The interviews conducted underlined the importance of the role of the Case Care Manager as a facilitator of the disease path that patients are experiencing both in terms of the clinical and psychological aspects but also as a support in managing daily life. future research should investigate the role of the Case Vare manager in meeting these needs